Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records - Wells, Alice; de Moor, Ferdinand C. (Zootaxa, 2020)
A collection of microcaddisflies from sites on the Cuito, Cuanavale, Cuembo, Cuando, Cubango, and Lungue Bungo Rivers in Angola has yielded seven new species and led to new records for a further five species. The new species include Hydroptila cuembica sp. nov., Hydroptila moxica sp. nov., Oxyethira palisada sp. nov., Orthotrichia ferreirae sp. nov., Or. meyi sp. nov., and Or. mlamboi sp. nov., and another species for which we erect a new genus, Aenigmatrichia asymmetrica gen. et sp. nov. The new records are for Catoxyethira kunenica Mey & de Moor 2019, Hydroptila brigittae Gibon 1987b, Hydroptila cruciata Ulmer 1912, Hydroptila maoae Gibon, Guenda, & Coulibaly 1994, Oxyethira sechellensis Malicky 1993, and a larva identified as that of a species of Tricholeiochiton. Beyond the known Angolan microcaddisfly fauna we resolve several taxonomic problems: We refer to Orthotrichia a species described by Jacquemart in Hydroptila, to become Orthotrichia trifurcata (Jacquemart 1962), comb. nov., with Orthotrichia hydroptiloides Wells & Andersen 1995 (from Tanzania) as a junior synonym; and we recognise Orthotrichia kivuensis Jacquemart 1956 (from Bukana, on Lake Kivu) as a junior synonym of Or. sanya Mosely 1948a from the Orange and Fish rivers. A list is given of the 16 microcaddisfly species now known from Angola: Representation is probably typical of sand and silt-based streams and pools, with the exception of Catoxyethira and Orthotrichia.